MENINGKATKAN BERPIKIR KRITIS, KREATIF, HASIL BELAJAR PAI MELALUI MODEL PETA KONSEP KELAS II SD - Ngademi (Profesi | Jurnal Ilmu Pendidikan dan Keguruan, 2014)
Focused on the central issue , how teachers can improve student learning outcomes in the eyes of Islamic Education Learning ( PAI ) in class II SDN Kedaung evening Kaliangke 07 West Jakarta . From the preliminary data collected by the researchers , suggests that student learning outcomes in the five times daily tests have not been able to reach the limit value KKM is 60 . For that researchers conduct action research in science class II on pembelajarn using Learning Model Concept Map ( Mind Mapping ) . The goal is : To find out how improving student learning outcomes after using the Learning Model Concept Map ( Mind Mapping ) 3 ) To determine how students' perceptions of Islamic Education Learning ( PAI) using a Learning Model Concept Map ( Mind Mapping ) .Data collection techniques used were : observation , interviews , questionnaires and exercises . The subjects were second grade students of SDN 07 evening Kedaung Kaliangke West Jakarta totaling 28 students consisted of 15 students and 13 female students daughters son . The results showed 1 ) Teachers only use the lecture method in teaching , so that students feel bored and assume Learning Islamic Education ( PAI ) is a tedious learning . 2 ) An increase in student learning outcomes significantly after using the Learning Model Concept Map ( Mind Mapping ) in Learning Islamic Education ( PAI ) is the learning outcomes of all students over the limit KKM . 3 ) The occurrence of a change of perception , students do not view Islamic Education Learning ( PAI ) as learning boring , but fun into learning